Oxford International Primary English Book 1 - Anna Yeomans (Oxford University Press)
The "Oxford International Primary English Workbook 2" is designed for young learners in Class 2, providing a comprehensive resource to support their English language development. Published by Oxford University Press, the workbook aligns with the Oxford International Primary English series, which is known for its structured and engaging approach to teaching English.
Keywords: Textbook English -- Workbook